2008
DOI: 10.1063/1.2937729
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative analytical model for static dipolar disorder broadening of the density of states at organic heterointerfaces

Abstract: Understanding the electronic structure of organic-organic heterointerfaces is crucial for many device applications of organic semiconductors. Here we have developed a simple analytical model to describe the effect of static dipolar disorder in a polymer dielectric on the density of states of an adjacent organic semiconductor. The degree of energetic disorder varies strongly with distance from the interface. Using a simple mobility model, we have been able to explain quantitatively both the magnitude as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(115 citation statements)
references
References 17 publications
5
110
0
Order By: Relevance
“…In another paper the same authors showed that for 235302-4 a poly(triarylamine) (PTAA) OFET the slope of the mobility versus gate bias curve depends on temperature. 17 After an initial steep rise at low gate bias, the mobility decreases with increasing gate bias at 300 K, whereas it continues to increase at 170 K. Again, such behavior is anticipated for intermediate disorder strength.…”
Section: Resultsmentioning
confidence: 82%
“…In another paper the same authors showed that for 235302-4 a poly(triarylamine) (PTAA) OFET the slope of the mobility versus gate bias curve depends on temperature. 17 After an initial steep rise at low gate bias, the mobility decreases with increasing gate bias at 300 K, whereas it continues to increase at 170 K. Again, such behavior is anticipated for intermediate disorder strength.…”
Section: Resultsmentioning
confidence: 82%
“…Here charge motion is not only related to the intrinsic properties of the semiconductor layer but also to processes taking place at the organic-dielectric interface. For example, Fröhlich polarons form in devices fabricated on high-k inorganic dielectrics (strong coupling regime) (19,24), and broadening of the density of states occurs due to static dipolar disorder in devices with polymeric dielectrics (weak coupling) (25,26). As a consequence, the charges become localized, their mobility is reduced, and, in some cases, depending on the strength of the coupling, the transport becomes thermally activated.…”
Section: Significancementioning
confidence: 99%
“…In the static limit, the polarization acts instead as an additional source of disorder, due to the random arrangement of charged dipoles in the substrate. [55,25] Both effects can convert the "bandlike" temperature dependent mobility intrinsic to organic semiconductors into a thermally activated behavior, and will not be considered here.…”
Section: Molecularmentioning
confidence: 99%